2022
DOI: 10.1142/s0217732322501528
|View full text |Cite
|
Sign up to set email alerts
|

Kaniadakis holographic dark energy in Brans–Dicke cosmology

Abstract: By using the holographic hypothesis and Kaniadakis generalized entropy, which is based on relativistic statistical theory and modified Boltzmann–Gibbs entropy, we build Kaniadakis holographic dark energy (DE) model in the Brans–Dicke framework. We derive cosmological parameters of the Kaniadakis holographic DE model, with IR cutoff as the Hubble horizon, in order to investigate its cosmological consequences. Our study shows that even in the absence of an interaction between the dark sectors of the cosmos, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 96 publications
0
16
0
Order By: Relevance
“…However, since radiation effects are dominant in the early Universe only, we expect they do not spoil considerably our predictions for the current and future epochs. Additionally, we aim at investigating the correspondence between our model and HDE based on other extensions of Boltzmann-Gibbs entropy, such as Tsallis [59,[80][81][82][83] and Kaniadakis [60] holographic dark energy. Also, interesting results could be found by connecting BHDE and dark energy model based on Gurzadyan-Xue framework.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since radiation effects are dominant in the early Universe only, we expect they do not spoil considerably our predictions for the current and future epochs. Additionally, we aim at investigating the correspondence between our model and HDE based on other extensions of Boltzmann-Gibbs entropy, such as Tsallis [59,[80][81][82][83] and Kaniadakis [60] holographic dark energy. Also, interesting results could be found by connecting BHDE and dark energy model based on Gurzadyan-Xue framework.…”
Section: Discussionmentioning
confidence: 99%
“…In [24], the authors have shown that the non-interacting HDE with the Hubble radius as IR cutoff cannot explain the current accelerated expansion of Universe in the BD theory. While in a similar analysis, it has been shown that the Tsallis and Kaniadakis holographic dark energy, due to the generalized entropy, with the Hubble cutoff in the BD gravity, can lead the accelerated Universe phase, even in the absence of interaction between two dark sectors [59,60].…”
Section: Introductionmentioning
confidence: 90%
“…For our next purposes, it is now convenient to rewrite the modified Friedmann Equation (35) in the equivalent form…”
Section: Big Bang Nucleosynthesis In Kaniadakis Statisticsmentioning
confidence: 99%
“…The standard HDE scenario is built upon Bekenstein–Hawking entropy, which arises as the black hole application of the BGS one. However, in [ 13 , 14 , 15 , 32 ], a generalized HDE based on Kaniadakis entropy has been investigated along with its implications on the cosmic evolution and thermal properties of the Universe (see also [ 23 , 24 , 33 , 34 , 35 ] for further applications). Remarkably, it has been shown that Kaniadakis dark energy exhibits peculiar features that do not have any correspondence in the traditional HDE, potentially providing a way to alleviate the Hubble tension.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these models is examined in different structures and conditions. The results are evaluated and compared with the latest observable data [41][42][43]. As mentioned, one of the most famous models in describing the nature of dark energy is a scalar field theory called quintessence, which represents a scalar field with a parameter (Q) and a decreasing potential.…”
Section: Introductionmentioning
confidence: 99%